2015
DOI: 10.1021/acs.iecr.5b03044
|View full text |Cite
|
Sign up to set email alerts
|

Global Kinetic Study of NO Reduction by NH3 over V2O5–WO3/TiO2: Relationship between the SCR Performance and the Key Factors

Abstract: The nonselective catalytic reduction (NSCR) reaction and the catalytic oxidation of NH3 to NO (C–O reaction) simultaneously happened during the selective catalytic reduction (SCR) of NO with NH3 over V2O5–WO3/TiO2, especially at higher temperatures. There was an excellent linear relationship between the SCR reaction rate and gaseous NO concentration, and the intercept and slope can be used to describe the rate constant of NO reduction through the Langmuir–Hinshelwood mechanism and that through the Eley–Rideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…As for NO and N 2 O in Figure 6a,b, all those N 2 peaks would be associated with ammonium ions and NH x on Bronsted and Lewis acid centers [43][44][45]. The NH x species are oxidized to N 2 via NO-assistant route, as discussed [11,39,48]. The presence of Fe 2 O 3 in VWT and c-VWT caused not only a shift of the major N 2 peak to lower temperatures, by 5-15 • C, but also a significant increase in their intensity, and such changes were greater for the commercial-based catalysts (Figure 6c(S3,S4)).…”
Section: Role Of Fe 2 O 3 Species For the Suppression Of N 2 O Formationmentioning
confidence: 78%
See 2 more Smart Citations
“…As for NO and N 2 O in Figure 6a,b, all those N 2 peaks would be associated with ammonium ions and NH x on Bronsted and Lewis acid centers [43][44][45]. The NH x species are oxidized to N 2 via NO-assistant route, as discussed [11,39,48]. The presence of Fe 2 O 3 in VWT and c-VWT caused not only a shift of the major N 2 peak to lower temperatures, by 5-15 • C, but also a significant increase in their intensity, and such changes were greater for the commercial-based catalysts (Figure 6c(S3,S4)).…”
Section: Role Of Fe 2 O 3 Species For the Suppression Of N 2 O Formationmentioning
confidence: 78%
“…An intensity of the 650-680 • C N 2 O peak in VWT and 2.73% Fe 2 O 3 /VWT (S1 and S2) was very weak compared to that in the other samples (S3 and S4), which is in excellent agreement with the H 2 O production levels ( Figure 5b). All the unpromoted catalysts (spectra S1 and S3 in Figure 6b , is improbable and NH species on V 5+ =O sites reacts with gas-phase NO to form N 2 O and V 4+ -OH [11,39,48]. This represents that gaseous NO is essential for such N 2 O production, suggesting an involvement of NO molecules shown in Figure 6a because of no feed of NO upon NH 3 TPD experiments.…”
Section: Role Of Fe 2 O 3 Species For the Suppression Of N 2 O Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…Xiong [9] completed a thorough kinetic study of the SCR system and included the NSCR and the deep oxidation of NH 3 to NO. They showed that higher amounts of NO and NH 3 (in equimolar ratios) produced less N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…The renewed interest in N 2 O, which is normally present in the ppm range in the normal SCR reaction, is due to its high (298 times that of CO 2 ) global warming potential [8]. A recent experimental study examines the formation of N 2 O over V 2 O 5 -WO 3 /TiO 2 catalysts [9]. This thorough study covers a wide range of temperatures from 150 to 500 °C, NO contents up to 1000 ppm and V 2 O 5 contents from 1 to 5 wt%.…”
Section: Introductionmentioning
confidence: 99%